Mentoring as a Form of Transformation in Academia - Hleliwe Khumalo; Ayanda Kevin Ndlovu (African Journal of Inter-Multidisciplinary Studies)
A considerable amount of literature has established the under-representation of Black women academics in South Africa and abroad.  Several factors continue to contribute to the lack of transformation in most institutions of higher learning in the country. Despite this challenge, a number of women have managed to succeed irrespective of the institutional culture and structures of exclusion. This study explored literature on mentoring as a tool for Black African women and underrepresented minority groups within the academic space to enhance diversity, equality, and inclusion. The study has shown the impact of mentorship in giving women an opportunity to grow and advance within the academic space and the importance of representation.